Revolutionaries or technocrats? - Knapp, A; Knapp, Andrew Francis (1984)
﻿ The thesis concerns the administration of a major French city by a Communist municipality working under the conservative governments of the Fifth Republic from 1965 to 1980. It tries to answer two main questions: how far French municipalities were free to produce their own policy outputs independently of central government, and what the French Communist Party (PCF) sought to gain from its successes in local government during the 1960s and 1970s. Particular (though not exclusive) attention is given to urban and regional planning because it shows the long-run effects of Communist municipal policy; the extent to which the municipality established an ongoing working relationship with its partners, including the State authorities; and the extent to which the PCF managed to integrate the urban environment, as a new political issue, into its local strategy. The official Communist approach to local government is examined through the Party's press, and compared with the work of the 'French school' of Marxist urban sociology that flourished in the early 1970s. There follows an historical introduction to Le Havre and an analysis of the PCF's sources of electoral strength; of the municipality's organisation and its relations with the Party apparatus and the public; of municipal finance under the Communists; and of the other main actors in the planning process. The planning outputs themselves - both structure plans and specific building projects sponsored by the municipality - are then analysed in the context of national legislation, market forces, and official Communist ideology. The originality of policy outputs is found to be real but limited. The limitations are due not only to legal and financial constraints but to the Communists' use of local office to prove their governmental credentials more than their revolutionary ones.